Cyberspace - Abu-Taieh, Evon; El Mouatasim, Abdelkrim; Al Hadid, Issam H. (IntechOpen, 2020)
Parallel to the physical space in our world, there exists cyberspace. In the physical space, there are human and nature interactions that produce products and services. On the other hand, in cyberspace there are interactions between humans and computer that also produce products and services. Yet, the products and services in cyberspace don't materialize-they are electronic, they are millions of bits and bytes that are being transferred over cyberspace infrastructure.